Integrating Musculoskeletal Education and Patient Care at Medical Student−Run Free Clinics. Issue 11 (5th April 2017) - McQuillan, Thomas; Wilcox‐Fogel, Nate; Kraus, Emily; Ladd, Amy; Fredericson, Michael
Abstract: Background: Student‐run free clinics (SRFCs) have emerged as an important educational component of United States (U.S.) medical schools. Despite the prevalence of musculoskeletal (MSK) problems presenting to SRFCs, students and clinics are often unprepared to diagnose and to treat common MSK complaints. Objective: We sought to determine the scope of diagnosis and treatment at a medical student−run free clinic specializing in musculoskeletal care using physical medicine and rehabilitation (PM&R) residents. Secondary goals included reviewing student satisfaction and determining the appropriateness of the clinic in medical education. Design: Retrospective chart review, anonymous online survey. Setting: Primary care, free student clinic affiliated with tertiary academic medical center. Participants: A total of 20 medical student volunteers, 6 PM&R residents, and 91 community patients. Methods: We established a musculoskeletal clinic as a specialty referral clinic for the 2 primary care SRFCs with institutional support from a partner medical school. We then reviewed clinical operations retrospectively using electronic medical records and student satisfaction based on an online survey. Main Outcome Measurements: We analyzed patient demographics and chief complaints, referrals provided, and medical services rendered. We also used a 5‐point Likert scale to assess student satisfaction. Results: A monthly musculoskeletal referral clinic was established with the oversight of PM&R attendings and residents. The clinic received 91 referrals and managed 61 unique patients over a 2.5‐year study period. The most common presentations to the clinic involved knee pain (n = 17, 27.9%) and back pain (n = 16, 26.2%). Pro bono relationships with community and institutional partners enabled all patients to receive medical examinations, physical therapy visits, plain film radiographs, and insurance consultations free of charge. Student satisfaction with teaching and patient care was high, with 19 of 20 students reporting their experience as "good" or "excellent." Conclusions: SRFCs represent an underused opportunity to enhance MSK education among medical students by treating a variety of common MSK complaints in an underserved population. Level of Evidence: Not applicable.